THORACODORSAL ARTERY PERFORATOR FLAP FOR UPPER LIMB RECONSTRUCTION - Haq, Ehtesham Ul; Javaid, Rana Hassan; Hameed, Shahid; Saood, Rao; Majid, Abdul; Waqas, Muhammad; Aslam, Ayesha; Yusuf, Omamah (Journal of Ayub Medical College Abbottabad, 2015)
Background: Thoracodorsal artery perforator flap (TAP) is a feasible option to reconstruct defects in upper limb where only skin and subcutaneous tissue is required. Methods: This case series was carried out at department of Plastic and Reconstructive Surgery Combined Military Hospital Rawalpindi. A total of 5 patients with upper limb defects were reconstructed with thoracodorsal artery musculocutaneous perforator flaps. Among them, 3 were pedicled and two free TAP flaps. All flaps except one pedicled flap were raised on a single perforator pedicle. Recipient sites were one axilla, two shoulder regions and two hands. The soft tissue defects in the patients had resulted from burns, trauma, wide local excision of synovial sarcoma and surgery for hidradenitis suppurativa. Preoperative hand held Doppler ultrasound was used to locate and mark the perforator. Results: All flaps survived without significant complications. All flaps were hyperemic in the immediate postoperative period. We designed and raised all the five flaps on eccentrically placed perforators. All the raised perforators originated from the descending branch of the thoracodorsal artery. The donor sites were closed primarily with linear scars in all cases except one, in which partial closure was accomplished with split thickness skin grafting (STSG). Conclusion: The thoracodorsal artery perforator flap has great potential for reconstructing large, relatively shallow, defects of upper limb because of its suitable skin quality, texture and appropriate thickness, as well as hidden donor site, a reliable pedicle and sparing of muscle unit. Keywords: Thoracodorsal artery perforator flap, Upper limb reconstruction, Hidradenitis suppurativa, Synovial sarcoma